e-Technologies and Networks for Development First International Conference, ICeND 2011, Dar-es-Salaam, Tanzania, August 3-5, 2011. Proceedings - Yonazi, Jim James; Sedoyeka, Eliamani; Ariwa, Ezendu; El-Qawasmeh, Eyas.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book constitutes the proceedings of the First International Conferences on e-Technologies and Networks for Development, ICeND 2011, held in Dar-es-Salaam, Tanzania, in August 2011. The 29 revised full papers presented were carefully reviewed and selected from 90 initial submissions. The papers address new advances in the internet technologies, networking, e-learning, software applications, Computer Systems, and digital information and data communications technologies - as well technical as practical aspects.
Keywords: Computer science; Computer communication systems; Software engineering; Database management; Information storage and retrieval; Artificial intelligence; Computer Science; Information Systems Applications (incl. Internet).; Computer Communication Networks; Artificial Intelligence (incl. Robotics).; Information Storage and Retrieval; Software Engineering; Database Management; Electronic books